Elephant population control in African National Parks - Roy Bengis (Pachyderm)
Reviews the reasons behind the need to control elephant populations - land use conflict, restricted range etc. Outlines the ways in which the usual culling programmes were and are still carried out and then notes the alternative method of controlling the population in a specific area, translocation. This latter method at best can only be considered a short term alternative to a constantly rising population.